Pengaruh Variasi Konsentrasi NaNO3 pada Medium Raoof terhadap Kultivasi Spirulina Platensis - Iqbal Syaichurrozi; Wardalia Wardalia; Sharfan Dwicahyanto; Yustinus Selis Toron (Eksergi, 2022)
Nutrition is one of the factors that affect the growth of Spirulina platensis. The cultivation medium proposed by Raoof is a modified version of Zarrouk medium. Raoof medium requires less nutrients than Zarrouk medium but the biomass produced is almost the same. This study was conducted to vary the concentration of NaNO3 of 0.5; 1.5; 2.5; 3.5 g/L in Raoof medium to study its effect on growth and biomass composition of S. platensis. At each concentration of NaNO3 of 0.5; 1.5; 2.5; 3.5 g/L obtained the highest biomass concentration of 0.6425; 0.6455; 0.6745; 0,5193 g/L on days 12, 12, 12, 10. Concentration of NaNO3 of 2.5 g/L resulted in the highest specific growth rate of 0.1371/day and the lowest double time of 5.0566 days. In general, increasing the concentration of NaNO3 from 0.5 to 2.5 g/L increased the protein content from 33.30 to 36.98%. The addition of higher NaNO3 (3.5 g/L) actually decreased the protein content to 35.52%.